Eksistensi Budaya Pataheri Suku Nuaulu ditengah Arus Modernisasi pada Negeri Nuanea - Johan Tanamal; Lodewyk Nahuway; Hendry Ch. Soselissa (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2022)
The purpose of this study is to determine how Pataheri culture is practiced in the Nuaulu community at Nuanea village, Amahai district, central Maluku region and how the Nuaulu society views Pataheri culture in the present era. Data collection methods included observation, library research and interview. Meanwhile, the elders, the leader of the youth community, the village secretary and the ruler of Nuanea village serve as important informants. Through data reduction, data testing and conclusion, data were studied qualitatively to portray the full occurrence in accordance with reality in the field. The findings demonstrated that pataheri a five stages maturation process for Nuaulu boys in their villages was a sign that their tribe descendant from Patalima cluster in Maluku. Additionaly, the Nuaulu people have the opinion that modern knowledge and technological advancements are the not the main drivers of changing to Nuaulu society’s customs and culture as a part of one’s own identity is a shared obligation.